Congenital hypogonadotropic hypogonadism: implications of absent mini-puberty - Dwyer,AA; Jayasena,CN; Quinton,R (Minerva Endocrinologica, 2016)
The phenomenon known as "mini-puberty" refers to activation of the neonatal hypothalamo-pituitary axis causing serum concentrations of gonadotrophins and testosterone (T) to approach adult male levels. This early neonatal period is a key proliferative window for testicular germ cells and immature Sertoli cells. Although failure to spontaneously initiate (adolescent) puberty is the most evident consequence of a defective gonadotropin-releasing hormone (GnRH) neurosecretory network, absent mini-puberty is also likely to have a major impact on the reproductive phenotype of men with congenital hypogonadotrophic hypogonadism (CHH). Furthermore, the phase of male mini-puberty represents a key window-of-opportunity to identify congenital GnRH deficiency (either isolated CHH, or as part of combined pituitary hormone deficiency) in childhood. Among male neonates exhibiting "red flag" indicators for CHH (i.e. maldescended testes with or without cryptorchidism) a single serum sample (between 4-8 weeks of life) can pinpoint congenital GnRH deficiency far more rapidly and with much greater accuracy than dynamic tests performed in later childhood or adolescence. Potential consequences for missing absent mini-puberty in a male neonate include the lack of monitoring of pubertal progression/lack of progression, and the missed opportunity for early therapeutic intervention. This article will review our current understanding of the mechanisms and clinical consequences of mini-puberty. Furthermore, evidence for the optimal clinical management of patients with absent mini-puberty will be discussed.